Effect of Jigsaw vs. Traditional Group Work on 8 th Graders’ Basic Science Process Skills achievement in Laboratory - Saeeda Majeed, Rizwan Akram Rana (PJE, 2023)
The purpose of this study was to explore the effect of Jigsaw-I model of cooperative learning (CL) on achievement of basic science process skills of 8th graders while working in science laboratory. An experimental study using randomized pretest posttest control group design was conducted. Sixty four male students were randomly selected from two intact 8th grade classes, 32 students from each class. Each group of thirty two students was further randomly assigned to experimental and control groups. Experimental group performed the experiments in science laboratory by using Jigsaw-I (JI) whereas control group performed the same experiments through traditional group work (TGW). “Basic Science Process Skills Laboratory Achievement-Tests (BSPSLAT-I & II)”were used as pre and post- tests to collect the data. The data was analyzed through independent sample t-test and ANOVA. The results showed significantly higher achievement of basic science process skills in favor of Jigsaw-I as compared to traditional group work. Moreover Jigsaw-I proved to be a better science laboratory technique both for low and medium achievers to gain basic science process skills. This study has implications for elementary science teachers to apply Jigsaw-I while science laboratory work for students’ higher achievement in basic science process skills.